Plans for expanding nuclear power plants lack technological and economic foundations - Alexander Wimmers; Fanny Böse; Claudia Kemfert; Björn Steigerwald; Christian R. von Hirschhausen; Jens Weibezahn (DIW Weekly Report, 2023)
In mid-April 2023, the final three nuclear power plants in Germany will be taken offline permanently. At the same time, the energy crisis resulting from the Russian invasion of Ukraine has fueled calls for the construction of new nuclear reactors in Germany. A similar debate is taking place in many other countries in the context of the climate crisis. Since the 1950s, nuclear power has been one of the most expensive energy sources and remains so to this day. It is also not a quick solution, as it takes decades to build reactors. Moreover, no significant technological breakthroughs are foreseeable in the development of cost-competitive reactors; this applies to both SMR concepts ("small module reactors") with lower capacity as well as for other types of reactors, such as fast breeder reactors. There is growing acceptance in the energy system modeling community, which previously predicted a substantial nuclear share while underestimating renewable energy sources due to overoptimistic assumptions, that there are no breakthroughs on the horizon.
Keywords: L51; L94; Q48; 330; economics; energy system analysis; innovation; nuclear power; technology